Evaluating the Effectiveness of SIPD as a Tool for Strengthening Local Financial Governance at the BKPD of Bone Bolango Regency - Fauzan Djaka Achmad; Zuchri Abdussamad; Irawaty Igirisa (Lembaga Riset Ilmiah, 2026)
This study was motivated by the need to strengthen local financial management through the use of the Local Government Information System (SIPD) as a digital tool capable of enhancing transparency, accountability, and traceability in financial management processes. The objective of this study is to assess the effectiveness of the SIPD in local government financial management at the BKPD of Bone Bolango Regency, specifically regarding the entry of invoice data, verification of SPMs, and the issuance of SP2Ds. The study employs a descriptive qualitative approach using the case study method. Data were collected through observation, in-depth interviews, and document analysis involving BKPD staff and OPD treasurers involved in using the SIPD. The results indicate that the SIPD has helped make financial administration processes more orderly, well-documented, transparent, traceable, and accountable. However, its effectiveness has not yet been fully optimized due to remaining challenges such as input errors, incomplete documents, data inconsistencies, network disruptions, limited resources, and uneven understanding among officials. This study concludes that SIPD is effective as an instrument for strengthening local financial governance, but requires human resource capacity building, continuous training, strengthened coordination between the BKPD and OPDs, and periodic system evaluations.